Inclusion of fat in diets for early lactating holstein cows - Scheffel, Michael V.; Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
Twenty-four Holstein cows were used to study the effect of dietary fat on milk production and metabolic traits. Whole cottonseed and tallow were used as fat sources and substituted into the control diet on an isocaloric basis. Chopped alfalfa hay and grain sorghum silage constituted the forage in all diets. Treatments were balanced for parity, body weight, and previous lactation milk production or genetic potential (primiparous cows). Cows were housed in a tie-stall barn beginning 4 weeks prepartum, fed similar diets, and assigned to treatment on the day of calving. Diets were formulated to provide 3.3, 4.8 and 6.5% fat. Diets actually measured 2.1, 3.8, and 5.3% fat. Serum urea nitrogen and cholesterol increased with increased dry matter intake and with increasing dietary fat. Serum triglycerides decreased at parturition and were similar among diets through 20 days postpartum. Thereafter, cows fed the 2.1% fat diet had fewer serum triglycerides than cows receiving 3.8% and 5.3% fat diets. Similar differences were observed with regard to mammary uptake of triglycerides. Serum glucose peaked at calving in all cows and tended to be similar among diets. Glucose uptake by the mammary gland increased with milk production. Cows fed the 5.3% fat diet had less urine ketones by 3 weeks postpartum. Weeks to positive energy balance were 8, 7, and 5 for cows fed 2.1, 3.8, and 5.3% fat diets, respectively. Dry matter intake in kg/day and as a percentage of body weight tended to be greater in the high fat group after 3 weeks of lactation. Milk yield (total and 3.5% FCM) was similar among diets through 10 weeks of lactation. Thereafter, lactation curves in cows fed the 5.3% fat diet were more persistent. Similar trends were observed for milk fat and protein. Milk protein percentage was slightly depressed on the 5.3% fat diet, but protein yield increased.
Keywords: Cows; High-fat diets; Milk; Cholesterol